2022
DOI: 10.1097/gco.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Physicians and healthcare professionals as advocates for abortion care and reproductive choice

Abstract: Purpose of reviewThe current review discusses the overarching role of advocacy as a primary component of access to abortion care. Abortion is viewed differently from any other form of health care, resulting in a marginalized, but essential healthcare component: without ongoing effective and strategic advocacy, abortion will not become or remain available. Lack of access to abortion care disproportionately affects historically excluded communities. Recent findingsAdvocacy is core to the provision of sexual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies on clinician advocacy in SRH similarly have concluded that Abbreviation: PAA, professional association advocates community-building is critical due to its role in providing emotional support, information, motivation, and strength. 33,35 Our findings on the importance of peer support and community became even more critical after Dobbs, as antiabortion protesters and politicians have grown emboldened to further undermine SRH and attack those who advocate for or provide abortion. 19 The hostility and uncertainty amplified by Dobbs may contribute further to clinician burnout, pointing to the need for a strong and sustainable community that provides motivation and resources, assists in setting boundaries, and shares in the physical and emotional burdens of this work to ultimately enhance leaders' resiliency.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies on clinician advocacy in SRH similarly have concluded that Abbreviation: PAA, professional association advocates community-building is critical due to its role in providing emotional support, information, motivation, and strength. 33,35 Our findings on the importance of peer support and community became even more critical after Dobbs, as antiabortion protesters and politicians have grown emboldened to further undermine SRH and attack those who advocate for or provide abortion. 19 The hostility and uncertainty amplified by Dobbs may contribute further to clinician burnout, pointing to the need for a strong and sustainable community that provides motivation and resources, assists in setting boundaries, and shares in the physical and emotional burdens of this work to ultimately enhance leaders' resiliency.…”
Section: Discussionmentioning
confidence: 96%
“…While some studies have explored perspectives on SRH clinician advocacy, programs that build PCC leadership in SRH remain under-researched. [33][34][35] Therefore, we aimed to qualitatively explore the Network's effectiveness in empowering clinicians to expand SRH access and to understand barriers and opportunities to strengthen the program's ability to meet SRH needs. With 42 independent clinics forced to close in the first 5 months following the Dobbs decision, clearly, evidence-informed strategies to expand SRH access are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Carrol et al provide a highly informative review on the role that physicians and healthcare providers can and should play as advocates for the care they provide and the patients for whom they provide it. In focusing on the ‘overarching role of advocacy as a primary component of access to abortion care’ the review ultimately underscores the findings that first, advocacy is core to the provision of sexual and reproductive health and second, community engagement coupled with advocacy skills assist providers to support access and combat inequities [5].…”
mentioning
confidence: 99%